Helminth infections in fish in Vietnam: A systematic review. (April 2021) - Nguyen, Trang Huyen; Dorny, Pierre; Nguyen, Thanh Thi Giang; Dermauw, Veronique
Abstract: In Vietnam, fisheries play a key role in the national economy. Helminth infections in fish have a major impact on public health and sustainable fish production. A comprehensive summary of the recent knowledge on fish helminths is important to understand the distribution of parasites in the country, and to design effective control measures. Therefore, a systematic review was conducted, collecting available literature published between January 2004 and October 2020. A total of 108 eligible records were retrieved reporting 268 helminth species, among which are digeneans, monogeneans, cestodes, nematodes and acanthocephalans. Some helminths were identified with zoonotic potential, such as, the heterophyids, opisthorchiids, the nematodes Gnathostoma spinigerum, Anisakis sp. and Capillaria spp. and the cestode Hysterothylacium ; and with highly pathogenic potential, such as, the monogeneans of Capsalidae, Diplectanidae and Gyrodactylidae, the nematodes Philometra and Camallanidae, the tapeworm Schyzocotyle acheilognathi, the acanthocephalans Neoechinorhynchus and Acanthocephalus. Overall, these studies only covered about nine percent of the more than 2400 fish species occurring in the waters of Vietnam. Considering the expansion of the aquaculture sector as a part of the national economic development strategy, it is important to expand the research to cover the helminth fauna of all fish species, to assess their potential zoonotic and fish health impacts. Graphical abstract: Image 1 Highlights: 268 helminth species were reported in 213 fish species occurring in Vietnam. Reported zoonotic helminths belonged to digeneans, nematodes and cestodes. Other species included monogeneans, nematodes, cestodes and acanthocephalans.